Fabrication and characterization of ZnO-rGO nanocomposite based schottky diode for UV detection - Pandey A.; Saha S.; Srivastava S.K. (My University, 2025)
Some investigations of ZnO-rGO nanocomposite thin films with various ratios of rGO and ZnO prepared by sol-gel method are done in this work. It is seen that the resistivity of samples decreas by increasing the rGO content in the composite films,. For photodetector application we have chosen a specific ratio of ZnO and rGO. The proposed and investigated structure Al/ZnO-rGO/Al photodiode detector has a high value of responsivity. The gain, defined as the ratio of illuminated current to dark current is also very high which is palpable from the results. The RA product and detectivity indicate that it is indeed a high speed detector characteristic. Hence the proposed ZnO-rGo composite structure may be utilized for making good photodetectors in UV region. © OSA 2014.